2016
DOI: 10.1371/journal.pgen.1006119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genetic Determinants of Erythrocyte Membrane Fatty Acid Composition among Greenlanders

Abstract: Fatty acids (FAs) are involved in cellular processes important for normal body function, and perturbation of FA balance has been linked to metabolic disturbances, including type 2 diabetes. An individual’s level of FAs is affected by diet, lifestyle, and genetic variation. We aimed to improve the understanding of the mechanisms and pathways involved in regulation of FA tissue levels, by identifying genetic loci associated with inter-individual differences in erythrocyte membrane FA levels. We assessed the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…Thus, uncorrected analyses of our data showed that L479 corresponded to higher levels of high-density lipoprotein and ApoA1 and lower levels of BMI (Table XI in Interestingly, in the final stages of the preparation of this article, a GWAS on erythrocyte membrane fatty acid composition among Greenlanders was published. 27 The study found that the CPT1A variant rs80356779 was associated with the levels of a range of fatty acids in the phospholipid fraction of erythrocyte membranes. These findings complement our serum metabolomics results in understanding the role of the p.Pro479Leu variant in CPT1A in regulating fatty acid levels in different blood components.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, uncorrected analyses of our data showed that L479 corresponded to higher levels of high-density lipoprotein and ApoA1 and lower levels of BMI (Table XI in Interestingly, in the final stages of the preparation of this article, a GWAS on erythrocyte membrane fatty acid composition among Greenlanders was published. 27 The study found that the CPT1A variant rs80356779 was associated with the levels of a range of fatty acids in the phospholipid fraction of erythrocyte membranes. These findings complement our serum metabolomics results in understanding the role of the p.Pro479Leu variant in CPT1A in regulating fatty acid levels in different blood components.…”
Section: Discussionmentioning
confidence: 98%
“…Details about the genotyping procedure and quality control have previously been described [25]. In total, 4674 individuals (IHIT, 2791; B99, 1336; BBH, 547) and 115,182 SNPs passed the quality control.…”
Section: Methodsmentioning
confidence: 99%
“…These discoveries include type 2 diabetes susceptibility variants in ABCC8 identified in Pima Indians , and in TBC1D4 identified in Greenlanders , as well as in SLC16A11 and HNF1A identified in the admixed Mexican population , where also a protective type 2 diabetes variant has been identified in IGF2 . Moreover, variants associated with lower lipid levels in APOC3 and DSCAML1 have been identified in an isolated Greek population , variants associated with levels of fatty acids in ACSL6 and CPT1A have been identified in Greenlanders , as well as variants associated with obesity in CREBRF and ADCY3 in Samoans and Greenlanders, respectively , and increased fasting insulin in AKT2 identified in Finns .…”
Section: Genetic Association Studies Of Metabolic Traits In Isolated mentioning
confidence: 97%
“…e The type 2 diabetes‐associated haplotype comprises rs13342232, rs13342692, rs117767867, rs75418188 and rs75493593 . f Strongest associated fatty acid for each variant .…”
Section: Genetic Association Studies Of Metabolic Traits In Isolated mentioning
confidence: 99%
See 1 more Smart Citation